Simultaneous and sequential influence of metabolite complexes of Lactobacillus rhamnosus and Saccharomyces boulardii and antibiotics against poly-resistant Gram-negative bacteria - O. Y. Isayenko; O. V. Knysh; O. V. Kotsar; T. N. Ryzhkova; G. I. Dyukareva (Regulatory Mechanisms in Biosystems, 2020)
For the first time the poly-resistant strains of Gram-negative microorganisms were studied for the sensitivity to combined simultaneous and sequential influence of metabolic complexes of Lactobacillus rhamnosus GG and Saccharomyces boulardii, obtained by the author’s method without using the growth media, with antibiotics. The synergic activity of antibacterial preparations and metabolic complexes of L. rhamnosus GG and S. boulardii were studied using modified disk-diffusive method of Kirby-Bauer. During the sequential method of testing (at first the microorganisms were incubated with structural components and metabolites, then their sensitivity to the antibacterial preparations was determined), we observed increase in the diameters of the zones of growth inhibition of Pseudomonas aeruginosa PR to the typical antibiotics (gentamicin, amіcyl, ciprofloxacin, сefotaxime) and non-typical (lincomycin, levomycetin) depending on the tested combinations. Acinetobacter baumannii PR exhibited lower susceptibility: growth inhibition was seen for the combination with ciprofloxacin, сefotaxime, levomycetin. Susceptibility of Lelliottia amnigena (Enterobacter amnigenus) PR increased to levofloxacin, lincomycin. The zones of growth inhibition of Klebsiella pneumoniae PR increased to gentamicin, amіcyl, tetracycline, сeftriaxone. Maximum efficiency was determined during sequential combination of antibiotics with separate metabolic complexes of L. rhamnosus and S. boulardii, and also their combination (to 15.2, 20.2 and 15.4 mm respectively) compared with their simultaneous use (to 12.2, 15.2 and 13.0 mm respectively) for all the tested poly-resistant pathogens, regardless of the mechanism of action of antibacterial preparation. Metabolic complexes of L. rhamnosus GG and S. boulardii, due to increase in the susceptibility of microorganisms, can decrease the therapeutic concentration of antibiotic, slow the probability of the development of resistance of microorganisms, and are therefore promising candidates for developing “accompanying medications” to antibiotics and antimicrobial preparations of new generation.